In Vitro Colonization of the Muscle Extracellular Matrix Components by Escherichia coli O157:H7: The Influence of Growth Medium, Temperature and pH on Initial Adhesion and Induction of Biofilm Formation by Collagens I and III - Chagnot, Caroline (Public Library of Science, 2013)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 are responsible for repeated food-poisoning cases often caused by contaminated burgers. EHEC infection is predominantly a pediatric illness, which can lead to life-threatening diseases. Ruminants are the main natural reservoir for EHEC and food contamination almost always originates from faecal contamination. In beef meat products, primary bacterial contamination occurs at the dehiding stage of slaughtering. The extracellular matrix (ECM) is the most exposed part of the skeletal muscles in beef carcasses. Investigating the adhesion to the main muscle fibrous ECM proteins, insoluble fibronectin, collagen I, III and IV, laminin-α2 and elastin, results demonstrated that the preceding growth conditions had a great influence on subsequent bacterial attachment. In the tested experimental conditions, maximal adhesion to fibril-forming collagens I or III occurred at 25°C and pH 7. Once initially adhered, exposure to lower temperatures, as applied to meat during cutting and storage, or acidification, as in the course of post-mortem physiological modifications of muscle, had no effect on detachment, except at pH(u). In addition, dense biofilm formation occurred on immobilized collagen I or III and was induced in growth medium supplemented with collagen I in solution. From this first comprehensive investigation of EHEC adhesion to ECM proteins with respect to muscle biology and meat processing, new research directions for the development of innovative practices to minimize the risk of meat contamination are further discussed.